2015
DOI: 10.1103/physreve.92.062306
|View full text |Cite
|
Sign up to set email alerts
|

Charged hydrophobic colloids at an oil–aqueous phase interface

Abstract: Hydrophobic poly(methyl methacrylate) (PMMA) colloidal particles, when dispersed in oil with a relatively high dielectric constant, can become highly charged. In the presence of an interface with a conducting aqueous phase, image-charge effects lead to strong binding of colloidal particles to the interface, even though the particles are wetted very little by the aqueous phase. We study both the behavior of individual colloidal particles as they approach the interface and the interactions between particles that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…The crystal first melts by dislocation unbinding to an anisotropic hexatic fluid and then undergoes a continuous transition into an isotropic fluid. This scenario has been confirmed by numerical simulations [23] and colloidal experiments [7,8,24,25]. It is also understood that the 2D melting scenario depends considerably on the potential softness [26].…”
supporting
confidence: 56%
“…The crystal first melts by dislocation unbinding to an anisotropic hexatic fluid and then undergoes a continuous transition into an isotropic fluid. This scenario has been confirmed by numerical simulations [23] and colloidal experiments [7,8,24,25]. It is also understood that the 2D melting scenario depends considerably on the potential softness [26].…”
supporting
confidence: 56%
“…Previous work has shown that, when dispersed in similar oils, micronsized PHS-coated PMMA particles acquire a charge q of around +500 e, where e is the elementary charge [7,20]. While the charging mechanism is still incompletely understood [18,21,22], particle charging in our system is robust and reproducible [20]. To facilitate measurement of particle dynamics with confocal microscopy, we fluorescently dye the particles with absorbed rhodamine 6G [23].…”
Section: Methodsmentioning
confidence: 88%
“…As a simplest rough estimate one can approximate the phonon spectrum by its isotropic acoustic asymptote, Eqs. (16) and (29) as was done in Ref. [108] for a 2D OCP with logarithmic interactions.…”
Section: Appendix E: Harmonic Entropy Constant From Qca Dispersion Rementioning
confidence: 99%
“…When colloidal particles are trapped in oil/water or gas/water interfaces, electrical dipoles are usually associated with each interfacial particle [12]. As a result, the interaction between colloidal particles is similar to that between vertically oriented dipoles [13][14][15][16][17] and can be in the first approximation described by a pairwise repulsive inverse-power law (IPL) potential decaying as ∼ 1/r 3 with the interparticle separation r. Direct experimental measurements of colloidal interaction potential in such * Sergey.Khrapak@dlr.de † st.yurchenko@mail.ru systems by the laser tweezers method [15,16,18] or using other approaches [19] generally confirm this assumption, although it is also clear that actual interactions can be very complicated, particularly in the regime where the separation is comparable to the particle size [20]. A similar shape of the interaction potential is observed in twodimensional colloidal systems of paramagnetic particles exposed to an external magnetic field [21][22][23].…”
Section: Introductionmentioning
confidence: 99%